SIMULATION AND OPTIMIZATION AS A TOOL FOR THE DEVELOPMENT OF HIGH EFFECTIVE TECHNOLOGICAL SCHEMES OF DISTILLATION - A. V. Timoshenko; E. A. Anokhina (Российский технологический журнал)
Distillation is the most widely used methods to separate different industrial mixtures into pure components. This method has unfortunately been very energy intensive and requires a lot of heat. Mathematical modeling of the technological schemes of distillation is an effective method to improve existing and to create new industrial technologies. The work deals with the synthesis and optimization of the distillation schemes with the partially thermally coupled flows (PTCDS) to decrease energy consumption. An algorithm is presented of the step-by-step transformation of the technological scheme of conventional distillation into the PTCDS. Examples are given of several solutions for the separation of multicomponent hydrocarbon mixtures by conventional distillation and azeotropic mixtures of organic products by extractive distillation. The data are presented for the optimization algorithms of the PTCDS. A comparison is made of conventional and developed distillation schemes using the energy consumption criterion. It is shown that the systems with partially thermally coupled flows provides a significant up to 30% reduction in energy consumption.